Burkina Faso : Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
The Poverty Reduction Strategy Paper (PRSP) prepared by the Burkinabe government forms the principal benchmark for all development actors, and reaffirms the urgency of attacking poverty from a structural perspective. It is the primary tool for coordination of all interventions and of public aid to development. The partnership existing between the government and the various actors under the PRSP makes the latter a powerful tool for resource mobilization. Further more, the PRSP will help in a stable macroeconomic framework by strengthening budget management and public investments.